G304(P) A network approach to shared learning – improving the primary/secondary care interface to decrease unnecessary ed attendances and improve child health. (24th May 2017) - Williams, J; Srivistava, R; Robinson, G; Roland, D; Dykes, P; Ruggins, N
Abstract : Aims: To improve care and safety for CYP in East Midlands and identify those in need of urgent care in Children's Emergency department (CED). To defer unnecessary ED attendances and to update and refresh the knowledge of our East Midlands health care providers. Background: Increasing numbers of CYP attending our ED departments nationally and in East Midlands (variation for under 1 year olds of 370–831 cf National rate 694/1 00 000 1 with of course a cost to CCG's. Despite this UK children's health outcomes in the UK for many common and long term conditions cf European countries 2 and key areas are high infant deaths and deaths in CYP with long term conditions (LTC) – asthma the commonest LTC. (National infant mortality rate 4.1, East Midlands 4.3/1000 live births Feb 2016.) The majority of deaths in CYP from asthma occur outside hospital. 3 Against this overstretched, younger GPs and practice nurses (PN's) may not have had paediatric specific training. Early local audit reflected lack of understanding in referral pathways for paediatric advice (2014/15). 4 Methods: Local Children's ED clinicians agreed to provide small group scenario based training to GP's and PN's. The network developed CCG specific infographic data relating to cost, attendance and admissions for individual CCG's. Focus on encouraging written CYP specific asthma plans, inhaler technique training, thresholds for referral to ED. Results: The event was fully booked within days of advertisement and attendance 90% (32/36). Evaluation prior to event revealed 73% delegates had had no CYP asthma training for >2 years and 23%>10 years. 36% pre event were not confident about teaching or assessing inhaler technique while after event 89% were confident. 97% of respondents scoring as good or excellent. Higher CCG asthma plans% reflect trends in lower ED attendance. Conclusion: Improving ED and primary care communication creates and facilitates improved understanding, GP and PN, shared best practice knowledge improved, ongoing measurements plan to evaluate the association between CCG's with higher numbers of asthma plans in place and decreasing ED attendance are ongoing. REFERENCES: Atlas of variation in care www.chimat.org.uk/variation www.rcpch.ac.uk/improving-child-health/child-mortality/child-mortality National review of asthma deaths UK 2014 https://www.rcplondon.ac.uk/projects/national-review-asthma-deaths 'East Midlands GPs understanding of urgent care pathway for CYP – an audit'. Dr R Srivastava